A global perspective on the influence of the COVID-19 pandemic on freshwater fish biodiversity. (January 2021) - Cooke, Steven J.; Twardek, William M.; Lynch, Abigail J.; Cowx, Ian G.; Olden, Julian D.; Funge-Smith, Simon; Lorenzen, Kai; Arlinghaus, Robert; Chen, Yushun; Weyl, Olaf L.F.; Nyboer, Elizabeth A.; Pompeu, Paulo S.; et al.
Abstract: The COVID-19 global pandemic and resulting effects on the economy and society (e.g., sheltering-in-place, alterations in transportation, changes in consumer behaviour, loss of employment) have yielded some benefits and risks to biodiversity. Here, we considered the ways the COVID-19 pandemic has influenced (or may influence) freshwater fish biodiversity (e.g., richness, abundance). In many cases, we could only consider potential impacts using documented examples (often from the media) of likely changes, because anecdotal observations are still emerging and data-driven studies are yet to be completed or even undertaken. We evaluated the potential for the pandemic to either mitigate or amplify widely acknowledged, pre-existing threats to freshwater fish biodiversity (i.e., invasive species, pollution, fragmentation, flow alteration, habitat loss and alteration, climate change, exploitation). Indeed, we identified examples spanning the extremes of positive and negative outcomes for almost all known threats. We also considered the pandemic's impact on freshwater fisheries demand, assessment, research, compliance monitoring, and management interventions (e.g., restoration), with disruptions being experienced in all domains. Importantly, we provide a forward-looking synthesis that considers the potential mechanisms and pathways by which the consequences of the pandemic may positively and negatively impact freshwater fishes over the longer term. We conclude with a candid assessment of the current management and policy responses and the extent to which they ensure freshwater fish populations and biodiversity are conserved for human and aquatic ecosystem benefits in perpetuity. Highlights: The COVID-19 pandemic has influenced (or may influence) freshwater fish populations. We evaluated the potential for the pandemic to mitigate or amplify widely acknowledged, pre-existing threats. We identified examples spanning the extremes of positive and negative outcomes. We also considered the pandemic's impact on fisheries demand, assessment, research, and management interventions.